Produtividade, composição bromatológica e características de fermentação da silagem da rama de cultivares de mandioca - Goes, Larissa Hortencia Santos (2015)
Cassava is a widespread culture in the Northeast of Brasil and has great economic importance. Among the waste produced, the aerial part can be used for animal feed especially in the form of silage, being a food option in the dry season. The objective of this study was to evaluate and compare the productions of aerial part and roots, the chemical composition and fermentation characteristics of cassava cultivars derived from two locations of Sergipe, São Domingos and Lagarto. The varieties used were as 9783/13, Amansa Burro, BRS Caipira, BRS Poti branca, BRS Tapioqueira, BRS Verdinha, Caravela, Irará, Lagoão and Preta do Sul. The age cut for weighing and preparation of silage was 10 months and it were used PVC mini laboratory silos with 10 cm diameter and 30 cm in length, sealed with plastic caps and metal clamps. For each treatment were made six mini silos, 3 of each sampling point, a total of 60 replicates in a completely randomized design (CRD). After 180 days, the silos were opened and analyzed for bromatological and fermentative composition. It was observed that the cultivars BRS Poti Branca and Lagoão stood out in the municipality of São Domingo, especially on productivity. In the city of Lagarto, varieties with more interesting results in productivity were the Irará, 9783/13 and BRS Poti Branca. Regarding the quality of the silage, the BRS Caipria and Caravela cultivars showed the best results.